FAKTOR-FAKTOR PENDORONG PEMERINTAH LAOS MENINGKATKAN KERJASAMA BILATERAL MELALUI CROSS-BORDER TRANSPORT AGREEMENT DENGAN PEMERINTAH THAILAND PADA TAHUN 2005 - Dian Andari, Nyoman Ayu; Fasisaka, Idin; Widya Nugraha, A.A. Bagus Surya (CITIZEN CHARTER; Vol 1 No 2 (2019), 2019)
ABSTRACT Lao PDR that previously had cooperation in terms of export and import trade with Thailand, took steps to increase bilateral cooperation with Thailand Government. This was done through meetings in international fora. The cooperation finally resulted with the signing of MoU (Memorandum of Understanding) on Cross-Border Transport Agreement (CBTA) between Savannakhet, Lao PDR and Mukdahan, Kingdom of Thailand in 2005. This research would like to analyze the factor that triggered the Lao government to increase bilateral cooperation through CBTA with Thai government. There are several concepts used in this research, such as rational model actor and internal-external factor, while the locus of this research during 1999 until 2005. Key words: Landlocked country, cooperation, CBTA, rational actor model, internal external factor .